2013
DOI: 10.1007/s00011-013-0593-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced failure of the gut barrier is site-specific and inhibitable by growth hormone

Abstract: Endotoxemia can induce gut barrier failure in rats, and the ileum is the site of greatest risk. The GH can reduce the incidence of endotoxemia-induced gut barrier failure, but not the associated mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Therefore, the FD4 clearance is also employed as a good marker for intestinal mucosal barrier function. 25,36) In the present study, we found that BBR caused decreases in both serum D-lactate level and intestinal clearance of FD4. In addition, although there was no significant changes in histopathology among groups, the Chiu's scores assessed for intestinal mucosal injury were significantly decreased by BBR when compared with the peritoneal air exposure group.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, the FD4 clearance is also employed as a good marker for intestinal mucosal barrier function. 25,36) In the present study, we found that BBR caused decreases in both serum D-lactate level and intestinal clearance of FD4. In addition, although there was no significant changes in histopathology among groups, the Chiu's scores assessed for intestinal mucosal injury were significantly decreased by BBR when compared with the peritoneal air exposure group.…”
Section: Discussionsupporting
confidence: 59%
“…15,25) Briefly, a segment of terminal ileum with length of 8 cm was prepared, and the mucosa was everted. One end of the intestinal segment was ligated, and a gut sac was made by injecting 1.0 mL of KrebsHenseleit bicarbonate buffer from the other end.…”
Section: D-lactate (D-la) Determinationmentioning
confidence: 99%
“…LPS, an endotoxin produced by bacteria, is known to induce ER stress (32)(33)(34). It can directly cause intestinal epithelial cell apoptosis (35) and failure of intestinal barrier (36). Thus, we used CCD841 cells to determine whether IRE1␣ could affect the cytotoxic activity of LPS.…”
Section: Iec-specific Ablation Of Ire1␣ Results In Spontaneous Colitismentioning
confidence: 99%
“…These studies have indicated that the terminal ileum is the major site for observation of damage to gut barrier functions following exposure to various injuries. It is suggested that terminal ileum is the most sensitive section of the intestinal tract [9]. …”
Section: Methodsmentioning
confidence: 99%
“…The intestinal permeability was also determined by calculating intestinal clearance of fluorescein-isothiocyanate dextran (FD4) as described in the literature [9, 10]. Briefly, a segment of terminal ileum with length of 8 cm was prepared, and the mucosa was everted.…”
Section: Methodsmentioning
confidence: 99%